The principle of national sovereignty through the lens of Saint Andrew's Day National Assembly - Mitić Sara (Zbornik Radova Pravnog Fakulteta u Nišu)
The power that comes from the people and the power that belongs to the people is a principle that arose after the French bourgeois and American revolutions. In Serbia, it found its expression at the famous St. Andrew's Day National Assembly (1858). Although the national assembly was not envisaged in the legislation, under the Turkish Hatiserif (the Constitution of 1838), all political actors, the prince, the council oligarchy and supporters of the Obrenović dynasty saw a possible way out of the current political situation in convening this assembly. In this context, the paper first provides a historical overview of national assemblies in Serbia, including an insight into the political events preceding the St. Andrew's National Assembly (the rule of the Defenders of the Constitution, Tenka's conspiracy, and the adoption of the Law on the National Assembly of 28 October 1858). The author elaborates on the dissatisfactions of all factors in the country, the urban and rural population, certain authorities and the leading political forces, and discusses the circumstances that accelerated the convening of the National Assembly on St. Andrew's Day (30th November 1858). The reasons that contributed to the final decision on convening the Assembly can be seen through the letters exchanged by some actors of these events. The central part of the paper focuses on the process of convening St. Andrew's Day National Assembly in Belgrade and its subsequent sessions (from 30 November 1858 to 31 January 1859), including presentations of viewpoints and request, and the events during the three-day revolution (10th -12th December 1858). Then, the author discusses the outcomes of St. Andrew's Day National Assembly: the overthrow of Prince Aleksandar Karađorđević, the return of Prince Miloš Obrenović, and de facto disempowerment of the Council. St. Andrew's Day National Assembly contributed to legalizing the work of the national assembly as one of the bodies of the supreme authority but the most important outcome was the strengthening of people's awareness about national sovereignty